On the Biconservative Quasi-Minimal Immersions into Semi-Euclidean Spaces - Sen, Ruya Yeggin; Kelleci, Alev; Turgay, Nurettin Cenk; Canfes, Elif Ozkara (Springer Basel Ag, 2021)
In this paper, we study biconservative immersions into the semi-Riemannian space form R24(c) of dimension 4, index 2 and constant curvature c is an element of {0,-1,1}. First, we obtain a characterization of quasi-minimal proper biconservative immersions into R24(c). Then we obtain the complete classification of quasi-minimal biconservative surfaces in R24(0)=E24. We also obtain a new class of biharmonic quasi-minimal surfaces in E24.
Keywords: Biconservative immersions; quasi-minimal surfaces; biharmonic submanifolds; semi-Riemannian space forms; Primary 53C40; Secondary 53A35; 53C12